Engineering and analyses of a novel Catalan vault. (January 2023) - Savino, V.; Franciosi, M.; Viviani, M.
Highlights: Mechanical testing on meso /macro samples composing Ecorasillas Catalan vaults. Characterization of mechanical properties of raw excavation-earth tiles. Finite element simulations via homogeneous and multi-layer material approaches. Abstract: Among the techniques for constructing vaults without formwork, the most popular is the Catalan. The first layer of lightweight tiles called "Rasillas" is assembled to form a predeterminate shape that resist to loads despite its reduced thickness. Until the first layer is completed, a sticky, quick setting mortar supports the terracotta tiles. Once completed, the first layer of the vault acts as a temporary formwork to support the further layers of tiles and then become a part of the structure. This paper presents a numerical analysis of the mechanical behavior of a novel type of Catalan vault made of sustainable raw excavation-earth tiles called "Ecorasillas". The advantages and drawbacks of the Ecorasilla vaults are highlighted and their performances are compared with a second type of Catalan vault made of clinker bricks. Test results are used to improve the quality of the predictions of the FEM models.